Technological roles of microorganisms in fish fermentation: a review. Issue 6 (26th March 2021) - Xu, Yanshun; Zang, Jinhong; Regenstein, Joe M.; Xia, Wenshui
Abstract: Fermentation is an important way to process and preserve fish. It not only gives the product a unique flavor and texture, but it also contributes to increased nutritional value and better functional properties. The production of fermented fish relies on naturally occurring enzymes (in the muscle or the intestinal tract) as well as microbial metabolic activity. This review focuses on the role of microorganisms on texture change, flavor formation, and biogenic amines accumulation in fermented fish. In addition, the production conditions and the major biochemical changes in fermented fish products are also introduced to help understand the factors influencing the quality of fermented fish. Moreover, prospects for further research of fermented fish are discussed.